Integrating AI in IoT analytics on the cloud for healthcare applications - Mala, D. Jeya, 1974- (Advances in computational intelligence and robotics (ACIR) book series., 2022)
"The objectives of the book are to apply AI in edge analytics for healthcare applications and to analyze the impact of tools, techniques and security solutions in Edge Analytics for Healthcare"--